A user-centered approach to developing a new tool measuring the behavioural and social drivers of vaccination. Issue 42 (8th October 2021) - Wiley, K.E.; Levy, D.; Shapiro, G.K.; Dube, E.; SteelFisher, G.K.; Sevdalis, N.; Ganter-Restrepo, F.; Menning, L.; Leask, J.
Abstract: Background: Children around the world remain under-vaccinated for many reasons. To develop effective vaccine delivery programmes and monitor intervention impact, vaccine programme implementers need to understand reasons for under-vaccination within their local context. The World Health Organization (WHO) Working Group on the Behavioural and Social Drivers of Vaccination (BeSD) is developing standardised tools for assessing childhood vaccine acceptance and uptake that can be used across regions and countries. The tools will include: (1) a validated survey; (2) qualitative interview guides; and (3) corresponding user guidance. We report a user-centred needs assessment of key end-users of the BeSD tools. Methods: Twenty qualitative interviews (Apr-Aug 2019) with purposively sampled vaccine programme managers, partners and stakeholders from UNICEF and WHO country and regional offices. The interviews assessed current systems, practices and challenges in data utilisation and reflections on how the BeSD tools might be optimised. Framework analysis was used to code the interviews. Results: Regarding current practices, participants described a variety of settings, data systems, and frequencies of vaccination attitude measurement. They reported that the majority of data used is quantitative, and there is appetite for increased use of qualitative data. Capacity for conducting studies on social/behavioural drivers of vaccination was high in some jurisdictions and needed in others. Issues include barriers to collecting such data and variability in sources. Reflecting on the tools, participants described the need to explore the attitudes and practices of healthcare workers in addition to parents and caregivers. Participants were supportive of the proposed mixed-methods structure of the tools and training in their usage, and highlighted the need for balance between tool standardisation and flexibility to adapt locally. Conclusions: A user-centred approach in developing the BeSD tools has given valuable direction to their design, bringing the use of behavioural and social data to the heart of programme planning.